134 ADULT SAFEGUARDING, HUMAN RIGHTS AND PEOPLE LIVING WITH DEMENTIA IN NURSING HOMES: CO-PRODUCING RECOMMENDATIONS FOR BEST PRACTICE. (25th October 2022) - Donnelly, S; Brennan, HR; Quinlan, K; O'Shea, J; Quaid, K; Golden, F; Keating, M; Mackall, S; Parfitt, R; Paley, G
Abstract: Background: People living with dementia (PLwD) in nursing homes have the right to be safe and to live a life free from harm and abuse; all persons are entitled to this right, regardless of their circumstances or where they live. PLwD are at greater risk of abuse and neglect than those without a diagnosis. Such abuse often goes unnoticed, because dementia may affect a person's ability to recognise abuse or to report it. In 2021, the Alzheimer Society of Ireland's Irish Dementia Working Group (IDGW) commissioned the development of a briefing paper to outline the key issues relating to upholding the human rights and safeguarding of PLwD in nursing homes including concrete recommendations for policy and practice. Methods: A scoping review of the existing literature on this topic was carried out. This was supplemented by adopting a snowball strategy to identify additional relevant literature. Three co-design online sessions were convened with members of the IDWG in order to discuss and agree on the general content and members also provided suggestions for additional research or policy papers that should be included. Co-design sessions were also used to brainstorm and reach a consensus as a group on recommendations. Results: This project identified a number of specific risk factors for PLwD, including organisational abuse, the need to move towards a restraint-free environment, addressing barriers to reporting of abuse and promoting agency and autonomy within safeguarding processes. A number of policy and legislative gaps in our current adult safeguarding framework were identified making it more difficult to adequately protect PLwD in nursing homes. Conclusion: 22 recommendations for best practice were developed by the IDWG for nursing home service providers (public and private), health and social care practitioners, policymakers, the Department of Health, HIQA and political representatives in order to collectively advocate for meaningful change.